The Impact of Mountain Sports on Stress Reduction and Mental Health: A Review of Current Literature - Kret, Dominik Ireneusz; Szlachta, Wiktoria Klaudia (Quality in Sport, 2026)
In recent years, mountain sports have been gaining popularity as a form of physical activity that combines physical exertion with direct contact with nature and functioning in a demanding environment. The aim of this study is to present the current state of knowledge regarding the impact of mountain sports on stress reduction and mental health. The article discusses the physiological mechanisms of stress, the importance of physical activity for the functioning of the nervous system, and the role of the natural environment in the process of mental recovery. Particular attention is devoted to the phenomenon of “flow,” mental resilience, the prevention of depression and anxiety disorders, and the therapeutic use of outdoor activities. An analysis of available research indicates that mountain sports can contribute to improved well-being, reduced stress symptoms, and the strengthening of psychological competencies, such as emotional control and a sense of agency. At the same time, the article emphasizes the importance of adequate physical and mental preparation of participants and the necessity of conscious risk management associated with high-altitude activities.